ELEVATION OF THE CENTER OF ROTATION WITH THE USE OF JUMBO CUPS IN REVISION TOTAL HIP ARTHROPLASTY - A RADIOGRAPHIC STUDY - Maksim Zagorov; Kalin Mihov; Svetoslav Dobrilov; Gergana Nenova (Peytchinski Publishing, 2021)
Background: Acetabular revision with extra-large (jumbo) cementless cups is an effective treatment for many cavitary and segmental peripheral bone defects. However, hip center elevation may occur with the use of a jumbo cup owing to the superior direction of reaming and the increased diameter of the component compared with the native acetabulum. Purposes: The primary goal of this study was to evaluate the radiographically observed hip center elevation with the use of jumbo cups in acetabular and total hip revision at our institution. Materials and methods: We retrospectively reviewed control radiographic images of 43 consecutive patients treated with acetabular and total hip revision arthroplasty with a press-fit cementless cup. The difference between the height of the rotation center of the acetabular cup and the height of the rotation center of the contralateral native hip relative to the inter teardrop line was radiographically measured. Results: The radiographically measured mean elevation of the rotation center of the jumbo cup was 8,75 mm, which yielded an average increase in the height of the rotation centre of 83,6. A mean vertical shift of the rotation center of 0,72 mm was estimated for every 1 mm increase in the size of the jumbo cup. Conclusions: Our results indicate that the use of jumbo cups in revision hip arthroplasty leads to elevation of the rotation center of the hip with an average of 9 mm. This could be considered by the surgeon in an attempt to restore leg length, stability and biomechanics of the prosthetic hip.